Religiosity versus class existence: Indonesian Muslim middle class fashion consumption on Instagram - Sasiana Gilar Apriantika (Universitas Trunojoyo Madura, 2023)
This study aimed to see how the consumption behavior of the Muslim middle class through the digital space is within a dualistic view, namely as a religious identity or as an affirmation of class identity. This study used the Norman Fairclough Critical Discourse Analysis (CDA) method by analyzing three aspects: text, discursive analysis, and social practice. The scope of this research analysis is the content (in the form of posts) tagged on the official Instagram accounts of three Muslim fashion brands that produce Islamic clothing, namely (Brand A), (Brand B), and (Brand C). The results suggest that middle class Muslim fashion is no longer just an aspect of religiosity and religious identity, but has become a class affirmation. Social media postings using Muslim fashion brands (both A, B, and C) and then tagging them on the brands’ official Instagram accounts shows a strengthening of class identity. Identifying Muslim fashion by tagging the brands that appear can confirm that they are able to consume Hijabs and Muslim clothing are not only used to identify symbols of religion or religiosity, but more as symbols of social class. The use of Muslim fashion is not enough except to show class identity.